LINGKUNGAN KERJA PERAWAT BERBASIS VIRTUAL : Literature Review - Farah Nabilah (2020)
The virtual nurse-based work environment in the form of social media provides a variety of benefits to nurses. The purpose of this literature review is to analyze the literature on virtual-based work environments in the form of the benefits of using social media on nurses. Literature is obtained through Pubmed, Ebsco, Scopus databases by using the keywords "nurse", "nurses", "social media", "social networking", "benefit" and "advantage". Filtering and analysis using PICO and CRAAP methods. An initial search obtained 425 literature which was then screened to produce 6 literature for analysis. The most frequently used social media Facebook (50%), followed by Whatsapp and Twitter (33.33%), the benefits of social media are helping nurses to intervene online, seek health information, share health information, exchange experiences with other professionals, and communicate. The virtual nurse-based work environment as a whole can benefit nurses' work if used wisely. The hospital or management can consider the use of social media in the daily lives of nurses so as to provide convenience to the work of nurses.